On the question of the legality of Sufism within Islam. - Kartabayeva., E. T. (Journal of Oriental Studies, 2016)
This article deals with the problem of the sacred sources of Sufism. As known at the turn of XVІІ–XIX centuries under the influence of the colonial policy of Britain in Arabia, the Wahhabi movement emerged. The main purpose of the formation of the Wahhabi movement was the seed of discord within Islam as the main national ideology of the Muslim East, and thus ensuring the full conquest of the peoples of the region’s European colonizers. Wahhabis turned their weapons first against the Sufis, because at that period of history, Sufism was an influential force in the public life of Muslim countries. According to the author it is this particular historical circumstance influenced the continuing confrontation between these two streams of Islam. Having done a thorough analysis of the text of the Koran and Hadith the author comes to the conclusion that mystical knowledge - marifats are especially Sufism originates from Quranic aiyats and hadiths of the Prophet Muhammad.